A confusion of princes [compact disc, unabridged] - Nix, Garth (Random House/Listening Library, 2012)
"Battling aliens, space pirates, and competitors, Prince Khemri meets a young woman, named Raine, and learns more than he expected about the hidden workings of a vast, intergalactic Empire, and about himself"--